1988
DOI: 10.1177/002199838802200804
|View full text |Cite
|
Sign up to set email alerts
|

Residual Strength of a Carbon/Epoxy Composite Material Subjected to Repeated Impact

Abstract: The residual tensile and compressive strengths of specimens cut from composite plates subjected to repeated impact at various energy levels were measured. The 16-ply quasi- isotropic composite plates were 2 mm thick, fabricated from Hercules AS4/3501-6 car bon/epoxy prepreg. Impact energy level and number of impacts were found to be major factors influencing strength degradation. However, strength degradation was limited to the region near the impact point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…According to [11], in repeated impact tests an initial increase in the peak force is possible due to the compaction process of the thin layer of unreinforced resin at the impacted surface. At low impact energy levels, damage to the fibres near the surface is minimal and the compaction process provides a harder surface for the next impact.…”
Section: Resultsmentioning
confidence: 99%
“…According to [11], in repeated impact tests an initial increase in the peak force is possible due to the compaction process of the thin layer of unreinforced resin at the impacted surface. At low impact energy levels, damage to the fibres near the surface is minimal and the compaction process provides a harder surface for the next impact.…”
Section: Resultsmentioning
confidence: 99%
“…This reason among others, like the little number of machines producing cyclic impacts, makes that this field was invested little by researchers. The general assessment on various studies effectuated to date on impact fatigue, shows that no standard configuration of specimens nor of unified experimental device were adopted (Wyrick and Adams [1], Shin and Maekawa [2], Azouaoui et al [3]). …”
Section: Introductionmentioning
confidence: 99%
“…Compressive and tensile residual strengths of carbon/epoxy composites subjected to repeated impacts were measured by Wyrick and Adams [1]. The authors showed that impact energy level and impact number are the principal factors which influence the degradation of residual strength.…”
Section: Introductionmentioning
confidence: 99%
“…The damage caused by high-velocity impacts is typically visible and also decreases the laminate strength and elastic modulus [48]. As would be expected, penetration-induced fiber breakage is the primary damage mode of highvelocity impacts.…”
Section: Impact Behavior In Generalmentioning
confidence: 82%
“…This is done to understand the energy absorption capabilities of the material, which are an indicator of ductility or stiffness. Research conducted by Wyrick and Adams indicates that there is a minimum impact energy required to cause a reduction in a material's tensile strength [48]. This threshold incident impact energy is primarily affected by laminate thickness and the composite's constituent materials.…”
Section: Low-velocity Impact Behaviormentioning
confidence: 99%